PENGARUH EXPERIENCE TERHADAP BRAND LOYALITY M-PAYMENT SHOPEE PAY MELALUI MEDIASI EXPECTATION - Helinda, elin; Enas, Enas (Journal of Management Review, 2023)
The phenomena discovered in this study suggest that the Banjar occupation officer's performance is still subpar. This is influenced by leadership's subpar emotional intelligence and underwhelming teamwork. The aim is to understand how teamwork affects staff performance, how the emotional intelligence of leadership affects team collaboration, and how these three factors interact to affect staff performance. This study employed a descriptive verification method as its methodology. a finding that demonstrates that respondents' responses to emotional intelligence are generally positive. Additionally, the respondents' response to the officer's inconsistent performance received a respectable response. Data analysis revealed that leadership's emotional intelligence has a small but positive influence on worker performance. According to this, the performance of the staff won't necessarily improve if the leadership's emotional intelligence rises. Staff performance is significantly and positively impacted by team collaboration. This implies that as staff performance improves, team cooperation will as well. Employee performance is significantly and favorably affected by emotional intelligence in leadership and teamwork. To put it another way, if teamwork and emotional intelligence in leadership improve, employee performance will also rise.